Spillovers in Local Banking Markets - Garmaise, Mark J.; Natividad, Gabriel (The Review of Corporate Finance Studies, 2016)
How are neighboring firms affected when a bank learns more about a given firm? We analyze exchange-rate-induced movements of Peruvian firms across a threshold that governs their regulatory treatment by banks. Firms that cross the threshold supply more information to their banks and experience a substantial increase in financing. We find positive spillover effects: the neighbors of the above-threshold firms also experience increased financing. These spillovers are confined to neighbors sharing a bank, and the performance of new loans to these neighbors improves, suggesting that the bank has become better informed about other local firms. Received October 15, 2015; accepted May 16, 2016 by Editor Efraim Benmelech.